Interactions between depositional regime and climate proxies in the northern south china sea since the last glacial maximum - Wang, Xuesong; Zhong, Yi; Clift, Peter D.; Feng, Yingci; Wilson, David J.; Kaboth-Bahr, Stefanie; Bahr, André; Gong, Xun; Zhao, Debo; Chen, Zhong; Zhang, Yanan; Tian, Yuhang; et al. (Paleoceanography and paleoclimatology, 2023)
Sedimentary deposits from the northern South China Sea (SCS) can provide important constraints on past changes in ocean currents and the East Asian summer monsoon (EASM) in this region. However, the interpretation of such records spanning the last deglaciation is complicated because sea-level change may also have influenced the depositional processes and patterns. Here, we present new records of grain size, clay mineralogy, and magnetic mineralogy spanning the past 24 kyr from both shallow and deep-water sediment cores in the northern SCS. Our multi-proxy comparison among multiple cores helps constrain the influence of sea-level change, providing confidence in interpreting the regional climate-forced signals. After accounting for the influence of sea-level change, we find that these multi-proxy records reflect a combination of changes in (a) the strength of the North Pacific Intermediate Water inflow, (b) the EASM strength, and (c) the Kuroshio Current extent. Overall, this study provides new insights into the roles of varying terrestrial weathering and oceanographic processes in controlling the depositional record on the northern SCS margin in response to climate and sea-level fluctuations.
Online veröffentlicht am 6. März 2023
Gesehen am 22.11.2023